Turbine Design for Low Heat Organic Rankine Cycle Power Generation using Renewable Energy Sources - Susanto, Herry; Abdullah, Kamaruddin; Saepul Uyun, Aep; Muhammad Nur, Syukri; Meurah Indra Mahlia, Teuku (MATEC web of conferences, 2018)
In recent years, due to its feasibility and reliability, the organic rankine cycle has become a widespread concern and is the subject of research. In the organic rankine cycle system, the radial turbine component is a highly influential component of the high low performance resulting. This paper discusses the design of radial turbines for organic rankine cycle systems. The design stage consists of preliminary design and detail design with parametric methods on the working fluid R22 to determine the geometry and initial estimation of the performance of the radial turbine. After that, a numerical study of the fluid flow region in the radial turbine with R22 as the working fluid was performed. The analysis was performed using computational fluid dynamics of Autodesk Computational Fluid Dynamics Motion software on two models of real gas, k-epsilon and shear stress transport. From the results of this analysis, there is pressure, velocity and temperature distribution along the radial turbine blades and estimated performance under various operating conditions. Comparison between parametric and computational fluid dynamics analysis results show different performance. The difference is due to the computational fluid dynamics analysis already involving the real gas shear stress transport model.